(untitled) (KULT_online, 2010)
Katrin Dennerlein focuses in her 2009 thesis on the narrative construction and representation of space in fictional texts. The author attributes the process of mental reconstruction of the textually created space to a model-reader who draws conclusions according to the textual information and his general knowledge. This means that the space of the narrated world is a mental model by the model-reader. An interdisciplinary approach through the use of cognitive linguistics, psychology, geography, sociology, evolution psychology, and evolution biology is decisive for her study.